1990
DOI: 10.1007/bf00239996
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics of mycorrhizas and non-mycorrhizal roots of Norway spruce

Abstract: The occurrence and amount of soluble and insoluble phenolics in mycorrhizal and non-mycorrhizal roots of Picea abies (L.) Karst, were investigated, p-Hydroxybenzoic acid glucoside, picein, piceatannol and its glucoside, isorhapontin, catechin and ferulic acid could be identified by high-performance liquid chromatography in mycorrhizas of Picea abies-Lactarius deterrimus and Picea abies-Laccaria amethystea. Both types were collected from axenic cultures and the latter also from a spruce stand. The same phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 33 publications
0
42
1
Order By: Relevance
“…These types of stilbenes aglycones and glucosides have previously been discovered in bark extracts (Pietarinen et al 2006). Moreover, piceoside, piceatannol and its glucoside, and isorhapontin have been detected in P. abies roots (Münzenberger et al 1990;Latva-Mäenpää et al 2014). However, various reports did not find stilbenes in the hydrophilic knotwood extractives of P. abies (Willför et al 2003).…”
Section: Chemical Composition Of Wood and Bark Extracts Of Picea Abiementioning
confidence: 94%
See 2 more Smart Citations
“…These types of stilbenes aglycones and glucosides have previously been discovered in bark extracts (Pietarinen et al 2006). Moreover, piceoside, piceatannol and its glucoside, and isorhapontin have been detected in P. abies roots (Münzenberger et al 1990;Latva-Mäenpää et al 2014). However, various reports did not find stilbenes in the hydrophilic knotwood extractives of P. abies (Willför et al 2003).…”
Section: Chemical Composition Of Wood and Bark Extracts Of Picea Abiementioning
confidence: 94%
“…Previously, five benzoic acid derivatives (syringic acids, p-hydroxybenzoic, vanillic, and anisic), two cinnamic acid derivatives, p-coumaric, and ferulic acids were identified in P. abies cells (Metsämuuronen and Siren 2014). Native ferulic acid and phydroxybenzoic acid glucoside were found in root extracts (Münzenberger et al 1990). Various stilbenes and stilbenes glucosides have been previously observed in different parts of P. abies (Metsämuuronen and Siren 2014).…”
Section: Chemical Composition Of Wood and Bark Extracts Of Picea Abiementioning
confidence: 98%
See 1 more Smart Citation
“…P-Hydroxyacetophenone (pHAP) is an aromatic ketone ( Figure 1) having wide commercial applications. It is also known as piceol that is a phenolic compound and can be obtained naturally from mycorrhizal roots of Norway spruces (Picea abies) [5,6]. It is used in the production of rubbers, plastics, agricultural chemicals, and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…In incompatible pairings, phenolics accumulated in roots as a result of a hypersensitive reaction. In mycorrhizas of Picea abies, Larix decidua and Pinus sylvestris, a lower concentration of soluble and cell wall bound phenolics than in uninoculated roots was observed (Münzenberger et al, 1990(Münzenberger et al, , 1995(Münzenberger et al, , 1996. Later, they observed that laccase and peroxidase activities differed between mycorrhizas and uninoculated roots of P. abies and L. decidua (Münzenberger et al, 1997).…”
mentioning
confidence: 99%